Production of oceanic nitrous oxide by ammonia-oxidizing archaea - Löscher, Carolin; Kock, Annette; Koenneke, M.; LaRoche, Julie; Bange, Hermann W.; Schmitz, Ruth A. (Biogeosciences, 2012)
The recent finding that microbial ammonia oxidation in the ocean is performed by archaea to a greater extent than by bacteria has drastically changed the view on oceanic nitrification. The numerical dominance of archaeal ammonia-oxidizers (AOA) over their bacterial counterparts (AOB) in large parts of the ocean leads to the hypothesis that AOA rather than AOB could be the key organisms for the oceanic production of the strong greenhouse gas nitrous oxide (N2O) that occurs as a by-product of nitrification. Very recently, enrichment cultures of marine ammonia-oxidizing archaea have been reported to produce N2O. Here, we demonstrate that archaeal ammonia monooxygenase genes (amoA) were detectable throughout the water column of the eastern tropical North Atlantic (ETNA) and eastern tropical South Pacific (ETSP) Oceans. Particularly in the ETNA, comparable patterns of abundance and expression of archaeal amoA genes and N2O co-occurred in the oxygen minimum, whereas the abundances of bacterial amoA genes were negligible. Moreover, selective inhibition of archaea in seawater incubations from the ETNA decreased the N2O production significantly. In studies with the only cultivated marine archaeal ammonia-oxidizer Nitrosopumilus maritimus SCM1, we provide the first direct evidence for N2O production in a pure culture of AOA, excluding the involvement of other microorganisms as possibly present in enrichments. N. maritimus showed high N2O production rates under low oxygen concentrations comparable to concentrations existing in the oxycline of the ETNA, whereas the N2O production from two AOB cultures was comparably low under similar conditions. Based on our findings, we hypothesize that the production of N2O in tropical ocean areas results mainly from archaeal nitrification and will be affected by the predicted decrease in dissolved oxygen in the ocean.